Комплексний аналіз розвитку малого підприємництва в Кіровоградській області - Хачатурян, О. С.; Hachaturian, О. (КНТУ, 2013)
У статті визначено та проаналізовано основні показники, що характеризують стан розвитку малого підприємництва та зайнятості населення в Кіровоградській області у порівнянні із середньорегіональними та середньоукраїнськими показниками. Виявлено значні невідповідності між кількістю малих підприємств, зайнятістю населення та продуктивності праці на них і величиною заробітної плати для низки адміністративно-територіальних одиниць регіону. Намічено напрямок подальших досліджень. The aim of the paper is a comprehensive analysis of the state of small business in the Kirovograd region for integrated index reached its degree of development at the level (regions and cities of regional subordination) administrative units. The level of formation and development of small businesses should be analyzed by the integrated indices. The article outlines some of them: the coefficient of the number of small businesses, rate of employment in small enterprises, factor productivity of employees of small businesses, the rate of wage workers in small businesses. Analysis of the factors showed that none of the administrative units of the region does not have all the above indicators higher than the average for the area. A similar pattern is observed if we consider the position of administrative areas in the region for some indicators. Even lower levels of performance relative to the average in Ukraine. Only three administrative units of the region are considered indicators higher than the average for Ukraine. This state of small business and employment therein population other than critical, can not be determined. Therefore necessary to develop and implement a system of regional management and implementation of effective regional policies to support small businesses. Moreover, such a policy should be developed for each of the administrative-territorial units, combined with the level of employment in small business as defined by a comprehensive study examined indicators based on cluster analysis, which should determine the future direction of research.
Problems of development of small enterprise are in the Kirovograd area
Keywords: мале підприємництво; зайнятість населення; адміністративно-територіальна одиниця